2022
DOI: 10.1128/mbio.02886-21
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Is an Environmental Cue in the Gut for Salmonella enterica Serovar Typhimurium Biofilm Dispersal through Curli Repression and Flagellum Activation via Cyclic-di-GMP Signaling

Abstract: Recent studies provided important insight into our understanding of the role of c-di-GMP signaling and the regulation of enteric biofilms. Despite an improved understanding of how c-di-GMP signaling regulates S. Typhimurium biofilms, the processes that affect the intracellular c-di-GMP levels and the formation of multicellular communities in vivo during infections remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…During systemic infection, S. Typhimurium resides predominantly within the host macrophages [24]. Previous studies have reported that S. Typhimurium infection can stimulate iNOS and nitrate production in mouse macrophages [11], and the increase in nitrate levels in S. Typhimurium-infected RAW264.7 macrophages was also observed in this study. Concentrations of nitrate as high as 20 µM were detected in the supernatant of RAW264.7 cells during the 24 h infection period with S. Typhimurium (Figure 1a), and this is consistent with the data reported in previous studies.…”
Section: Nitrate Levels Are Increased During Systemic Infection By S ...supporting
confidence: 82%
See 2 more Smart Citations
“…During systemic infection, S. Typhimurium resides predominantly within the host macrophages [24]. Previous studies have reported that S. Typhimurium infection can stimulate iNOS and nitrate production in mouse macrophages [11], and the increase in nitrate levels in S. Typhimurium-infected RAW264.7 macrophages was also observed in this study. Concentrations of nitrate as high as 20 µM were detected in the supernatant of RAW264.7 cells during the 24 h infection period with S. Typhimurium (Figure 1a), and this is consistent with the data reported in previous studies.…”
Section: Nitrate Levels Are Increased During Systemic Infection By S ...supporting
confidence: 82%
“…As a stable derivative of NO, the levels of host-derived nitrate always increase due to the generation of NO upon S. Typhimurium infection. During infection of the intestine, S. Typhimurium can exploit this increased host nitrate to promote intestinal pathogenicity [11]. However, the functions of nitrate in the replication of S. Typhimurium within macrophages and in the systemic infection of S. Typhimurium are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron transport chain: proteins and organic molecules in the bacterial inner membrane that participate in redox reactions that translocate protons to the periplasm and ultimately shuttle electrons to a terminal electron acceptor. Energy metabolism: a set of biochemical reactions devoted to energy IR715 and increases motility, processes that may facilitate the spread of the pathogen in the inflamed gut [9]. In these examples, the ability of facultative anaerobic enterobacteria to use an array of AEAs represents a growth advantage over the native flora.…”
Section: Glossarymentioning
confidence: 99%
“…Similar biofilm control by the NarLX/NarPQ TCSs can be seen in human pathogen Burkholderia pseudomallei [ 71 , 89 ]. As nitrate and nitrite control and metabolism is central to many cellular processes, it is not surprising that many symbiotic and pathogenic bacteria have one or both of the previously described nitrogen-sensing TCSs or a homolog of these TCSs [ 22 , 25 , 90 ], though more detailed mechanistic research is necessary to link these nitrogen related TCSs directly to the modulation of virulence in more pathogens.…”
Section: Host Metabolic Products and Conditions As Tcs Triggersmentioning
confidence: 99%